TINJAUAN PELAKSANAAN PROGRAM USAHA KESEHATAN SEKOLAH DI SDN 01 TANJUNG GADANG KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA - Rindiani Rindiani; Zainur Zainur; Hirja Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this study is the lack of implementation of the school health business program (UKS) allegedly by the lack of school health education, lack of school health services, an unhealthy school environment at SDN 01 Tanjung Gadang, Lareh Sago Halaban sub-district, Lima Puluh Kota Regency as it should be, especially in terms of health education, health services and the school health environment. From this fact, a temporary hypothesis was taken that the implementation of UKS at SDN 01 Tanjung Gadang, Lareh Sago Halaban District, Lima Puluh Kota Regency was not going well. Knowing the implementation of a healthy school environment at SDN 01 Tanjung Gadang, Lareh Sago Halaban District, Lima Puluh Kota Regency. The population of this study was class I to VI, consisting of 90 sons and 87 daughters. The total number of students is 177 students. Based on the population above, sampling was carried out using the “Purposive Sampling” technique. Where in this study the sample used was 44 students consisting of 21 fourth grade students and 23 fifth grade students at SDN 01 Tanjung Gadang. The instrument in this study uses a questionnaire that will be distributed to the sample. The conclusions are from school health education with a score (91.25%), school health services with a score (79.28%), and a healthy school health environment with a score (82.65%). So the overall average score (84.4%) performed very well.Key Words: School Health Efforts, School Services, School Environment